Judicial Activism on Indonesia’s Constitutional Court Verdict on the Judicial Review of Job Creation Bills Number 6 of 2023 - Reyman Dhani Erwansyah; M. Rizqi Senja Virawan (Indonesian Journal of Administrative Law and Local Government, 2024)
A rule of law country is known by emphasizing the existence of separation of powers concept which is divided into the legislative, executive, and judicial powers or what is commonly referred to as judicial power. Constitutional courts are one of the manifestations of the judicial power with rights to keeping the dignity and supremacy of the constitution. Constitutional court’s judges had the right to take any actions to ensure the supremacy of the constitution is up held. Which the way is we knew as judicial activism. The practice of judicial activism commonly known and flourishes in countries with Anglo-Saxon traditions such as United States and United Kingdom. Judicial activism defined as a judicial behaviour where judges proactively interpret existing legal norms due to constitutional issues, especially in the context to uphold the constitutional supremacy. The methodology of this research is normative which is analysing how is applied in Indonesia particularly through the Indonesia’s Constitutional Court Verdict 168/PUU-XXI/2023 regarding the judicial review of Job Creation Bills Number 6 of 2023.